Interspecific variation in deterioration and degradability of avian feathers: the evolutionary role of microorganisms. (16th April 2020) - Azcárate‐García, Manuel; González‐Braojos, Sonia; Díaz‐Lora, Silvia; Ruiz‐Rodríguez, Magdalena; Martín‐Vivaldi, Manuel; Martínez‐Bueno, Manuel; Moreno, Juan; Soler, Juan José
Abstract : Feathers are essential for avian life, and factors affecting their integrity are important to understand their evolution. These factors should depend on, among other traits, species‐specific bacterial environments and life‐history characteristics. However, interspecific variation in feather deterioration, feather susceptibility to degradation by keratinolytic bacteria (degradability), and bacterial environment, have rarely been quantified. Here, we did so by measuring deterioration and degradability of wing feathers of fledglings in 16 bird species, and characterizing the bacterial environment where they developed. We found statistically significant interspecific variation for all considered variables. On average, non‐melanised were more deteriorated than melanised feathers, but differences depended on the species. Moreover, nest bacterial loads were related to feather wear, but the sign of the association depended on the bacterial group considered and on feather pigmentation. We also found a positive association of feather degradability with wear of non‐melanised feathers, and with bacterial loads. These results suggest that bacterial environments determine the integrity of fledgling feathers as well as their resistance to bacterial degradation, which implies a preponderant role of bacteria in driving the evolution of avian feathers.